2008
DOI: 10.1017/s136898000700002x
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric predictors for the risk of chronic disease in non-diabetic, non-hypertensive young Mexican women

Abstract: Objectives: To assess the ability of anthropometric measurements to identify young women at risk of developing diabetes, hypertension and heart disease in the future and to compare cut-off points for common anthropometric measures established with receiver-operating characteristic (ROC) curves with those reported in the literature. Design: Cross-sectional study. Subjects: Eight hundred and two young Mexican women living in semi-urban poverty. Measurements/methods: The ability of anthropometric measures of fatn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 51 publications
(109 reference statements)
1
7
2
1
Order By: Relevance
“…Few studies in populations of Asian origin have reported WHR to have superior predictive capacity than WC only, while similar studies in North American population have reported WC to be superior to WHR. [10] Although in our study, we found BMI and sum of skin fold thickness as the only two parameters suggesting an indicator of risk in prehypertensive subjects. The other parameters were not statistically significant; these values were similar to the study results of Neufeld et al [10] In the risk factor of hypertriglyceridemia, only BMI was the lone anthropometric indicator suggesting an correlating risk factor, and no other parameter suggested any relation, which is in conjunction to study predicted by Neufeld et al [10] Recent studies have produced differing conclusions about which anthropometric measure has the best predictive capacity for detecting disease risk.…”
Section: Discussioncontrasting
confidence: 55%
“…Few studies in populations of Asian origin have reported WHR to have superior predictive capacity than WC only, while similar studies in North American population have reported WC to be superior to WHR. [10] Although in our study, we found BMI and sum of skin fold thickness as the only two parameters suggesting an indicator of risk in prehypertensive subjects. The other parameters were not statistically significant; these values were similar to the study results of Neufeld et al [10] In the risk factor of hypertriglyceridemia, only BMI was the lone anthropometric indicator suggesting an correlating risk factor, and no other parameter suggested any relation, which is in conjunction to study predicted by Neufeld et al [10] Recent studies have produced differing conclusions about which anthropometric measure has the best predictive capacity for detecting disease risk.…”
Section: Discussioncontrasting
confidence: 55%
“…The psychosocial measures, including maternal depressive symptoms when the children were 15 months old (Time 1) were assessed as part of a sub-study (n=242) designed to look at maternal caregiving practices and growth and development outcomes 27. From April to August 2005 (Time 2), we attempted to relocate all women from the original sample with the objective of monitoring weight change and chronic disease risk factors over time 2830. Additional funds were obtained for the assessment of anthropometry, physical activity and potential predictors of these of a sample of 265 children.…”
Section: Methodsmentioning
confidence: 99%
“…In resource-poor countries, targeting high-risk people for preventive measures is likely to reduce both the economic and disease burden. High-risk groups can be identified by using anthropometric measurements, but cutoff values vary with country, population, and ethnic group 11 . Finding population-specific cutoff values for anthropometric variables is therefore useful for research and clinical practice 12 .…”
Section: Introductionmentioning
confidence: 99%